SPARC Knockdown Reduces Glutamate-Induced HT22 Hippocampal Nerve Cell Damage by Regulating Autophagy - Chen, Shuang; Zou, Qin; Guo, Qiang; Chen, Yongmin; Kuang, Xi; Zhang, Yukang; Liu, Yan; Wu, Wengang; Li, Ge; Tu, Linzhi; Tong, Jingyi; Li, Songrong; et al. (Frontiers in Neuroscience, 2021)
Oxidative glutamate toxicity is involved in central nervous system (CNS) diseases including epilepsy, Alzheimer’s disease (AD) and ischemic stroke. However, the molecular mechanism of nerve injury is not fully understood in CNS diseases. Here, we used the glutamate-induced nerve damage model to explore the molecular mechanisms affecting nerve damage. our experiment shows the expression of SPARC is increased in glutamate-induced HT22 hippocampal nerve injury, Meanwhile, the level of autophagy is also increased in glutamate-induced HT22 hippocampal nerve injury. In addition, we confirmed SPARC can regulate autophagy in HT22 hippocampal nerve cells through knockdown and overexpression of SPARC. However, SPARC knockdown can reduce the glutamate-induced HT22 hippocampal nerve injury by regulating autophagy. The expression level of SPARC is essential for CNS diseases. In conclusion, SPARC increases in glutamate-induced HT22 hippocampal nerve injury and SPARC knockdown can reduce the glutamate-induced HT22 hippocampal nerve injury by regulating autophagy. These suggest that SPARC plays a crucial role in nerve injury of CNS diseases such as epilepsy, AD, and ischemia.